2020
DOI: 10.1007/s42729-020-00197-y
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and Its Application Methods Improve Physiological Traits and Antioxidants in Triticum aestivum (L.) Under Cadmium Stress

Abstract: Plants are exposed to various abiotic stressors in agricultural systems, especially cadmium (Cd) stress, which hinders plant growth and development. The current study was conducted to assess the protective role of silicon (Si) application in two methods and to identify the optimum method of Si application for wheat plants grown hydroponically under the same levels of Cd stress. For this purpose, we used two different silicon (Si; 1 mmol L −1 Na 2 SiO 3) application methods (i.e., root application and foliar sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…It has been reported that Cd stress decreased the value of C E because Rubisco C E is involved in the consumption of CO 2 in the Calvin cycle of photosynthesis (Bokhtiar et al 2012) and in this study; the values of C E were considerably decreased under Cd stress (Table 5). Previously, various researchers have documented the Cdinduced reduction in P n , T r , and g s in different field crops (Rahman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that Cd stress decreased the value of C E because Rubisco C E is involved in the consumption of CO 2 in the Calvin cycle of photosynthesis (Bokhtiar et al 2012) and in this study; the values of C E were considerably decreased under Cd stress (Table 5). Previously, various researchers have documented the Cdinduced reduction in P n , T r , and g s in different field crops (Rahman et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the results of experiment showed that higher accumulation of ROS (e.g., H 2 O 2 ) significantly enhanced the lipid peroxidation rate (MDA content) and EL in wheat cultivars (Table 6). Previously, Cd stress-induced production of H 2 O 2 and MDA contents has been reported in many plant species including wheat (Rahman et al 2020), rapeseed (Hasanuzzaman et al 2017), and maize (Anjum et al 2016). Therefore, plants developed different enzymatic and non-enzymatic antioxidants to alleviate the adverse effects of Cd-induced oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations